Caracterización Físico - Química y determinación de actividad biológica del aceite esencial de las hojas de Renealmina thyrsoidea Subespecie thyrsoidea - Basantes Aguirre, Jessica Elizabeth (2015)
This study aimed to characterize the chemical and physical components of the essential oil from the leaves of Renealmia subspecies thyrsoidea, besides determining its antibacterial and antifungal activity to promote a precedent for the future realization of products from this plant. The essential oil of Renealmia thyrsoidea subspecies thyrsoidea was obtained by steam stripping. The physical properties were determined; refractive indices (1,481 g) and acid indices (22,581 g). The density value was 0,8685g. The chemical composition of OE was determined by gas chromatography coupled to mass spectrometry (GC/MS) and nuclear magnetic resonance 1H (NMR1H). There were 49 compounds identified wich representing 95,33% of the oil. The most representative compounds were sylvestrene (28,78%), camphene (8,53%), β-phellandrene (6,46%), z-neoridol (6,37%), aristolochene (4,34%), adomandreno (3,69%), ɤ-copaene (3,13%). The antioxidant activity was evaluated by two spectrophotometric methods: test DPPH and ABTS assay. The IC50 values obtained were 20,86 mg/mL for DPPH and 1,33 mg/mL for ABTS. Antimicrobial activity revealed better inhibition results than strains of Gram (-) Escherichia coli ATCC8739TM and Pseudomona aeruginosa ATCC9027TM a MIC of 0,347 mg/ml for both. Facing the yeast Candida albicans ATCC10231 was 1,389 mg/ml and Candida tropicalis ATCC13803 0,347 mg/ml. The characterization of the chemical composition and determining the biological activity of the essential oil leaves Renealmia thyrsoidea subspecies thyrsoidea showed similar data against preliminary investigations with the same it.